The Effects of Puppet Games from Cassava Leaves on the Self Efficacy of Elementary School Students - Dewi, Annisa Dianesti; Nurchayati, Afiffa Halila; Firmansyah, Aditya Ilham; Hertinjung, Wisnu Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
This research was conducted to determine the effect of the puppet game from cassava leaves on the self-efficacy of elementary school students. The independent variable in this study was a game of puppets from cassava leaves. While the dependent variable of this study is self-efficacy. The design used in this study is the Pre-Post Test One Group Design. The subjects were 207 elementary school students in class V and class VI in Surakarta. The chronology of the study is a pre-test subject were given using a scale for ± 10 minutes. The next step is treatment in the form of puppet play from cassava leaves in the experimental group for ± 35 minutes. During the treatment, the researcher made observations with reference to the checklist observation sheet. The last plot is the post-test using the same scale as the pre-test, but the item number is random. The results of this study showed significant effect of the puppet game of cassava leaves cannot improving students’ self-efficacy. However, the results show the descriptive analysis of the puppet game cassava leaves can boost self-efficacy elementary school students who are in the low category as much as 86%, in the category of pretty much as 26%, and the high category as much as 5%.